Micropopagation of Cryptocarya massoy (Oken) Kosterm. Trough Optimizing Callus Induction with Benzylaminopurine (BAP) Supplementation - Hanafi, Muhammad; Noli, Zozy Aneloi; Idris, M.; Hany, Iga Permata (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to evaluate the effect of BAP concentrations on explant response and callus formation in Massoia. The experiment was arranged in a Completely Randomized Design (CRD) with three BAP concentrations: 0.5 mg/L, 1.0 mg/L, and 1.5 mg/L, each with 24 replications. The culture medium used was Murashige and Skoog (MS), and observations were carried out for 7 days after planting. Parameters observed included the percentage of viable explants, browning, contamination, average callus formation, callus color, and texture. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level. The results showed that 0.5 mg/L BAP yielded the highest explant survival rate (54%), the lowest browning rate (13%), and 35% contamination. Meanwhile, 1.5 mg/L BAP produced the highest average callus formation (0.21) with compact texture and brown coloration. Although not statistically significant, BAP concentrations affected explant viability and callus formation. A concentration of 0.5 mg/L tended to be optimal for maintaining explant viability, while 1.5 mg/L was more effective in inducing callus. These findings provide a preliminary basis for optimizing Massoia tissue culture techniques.